CEREBROSPINAL FLUID DRAINAGE DEVICES: EXPERIMENTAL CARACTERIZATION - Bim, C.; Pinotti, M.; Camilo, J. R.; Maset, A. L.; Mansur, S. S.; Vieira, E. D. R. (Revista de Engenharia Térmica, 2013)
Hydrocephalus is a pathophysiology due to the excess of cerebrospinal fluid in the brain ventricles and it can be caused by congenital defects, brain abnormalities, tumors, inflammations, infections, intracranial hemorrhage and others. Hydrocephalus can be followed by significant rise of intraventricular pressure due to the excess of production of cerebrospinal fluid over the absorption, resulting in a weakening of intellectual functions, serious neurological damage (decreased movement, sensation and functions), critical physical disabilities and even death. A procedure for treatment involves the placement of a ventricular catheter into the cerebral ventricles to divert/drain the cerebrospinal fluid flow to a bag outside of the patient body – provisory treatment known as external ventricular drainage (EVD). Another option is the permanent treatment, internal ventricular drainage (IVD), promoting the cerebrospinal fluid drainage to other body cavity, being more commonly the abdominal cavity. In both cases, EVD and IVD, it is necessary to use of some type of neurological valve in order to control the flow of cerebrospinal fluid. In the present work is proposed an experimental procedure to test the hydrodynamic behavior of a complete drainage system, or parts of them, in order to verify its performance when subjected to pressure gradients found in the human body. Results show that the method is well adapted to quantify the pressure drop in neurological systems.